A New Agenda For Football Crowd Management Reforming Legal and Policing Responses to Risk - Pearson, Geoff; Stott, Clifford (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book provides a holistic and interdisciplinary focus on the legal regulation and policing of football violence and disorder in Britain. Anchored in ground-breaking ethnographic and participant-action research, the book combines a crowd psychology and socio-legal approach to critically explore the contemporary challenges of managing football crowds. It sets out the processes by which football disorder occurs and the limitations of existing approaches to policing 'football hooliganism', in particular the dominant focus on controlling 'risk supporters', before setting out proposals for fundamental reforms to both law and policing. This book will be of value to academics, students, legal and policing practitioners, as well as policy-makers. The two authors are internationally known experts in the management and behaviour of football crowds and bring together for the first time over 30 years of research in this area from the disciplines of law and social psychology. Geoff Pearson is Professor of Law at The University of Manchester and Academic Director of the N8 Policing Research Partnership, UK. He was awarded his PhD on 'Legal Responses to Football Crowd Disorder' in 1999 and has published extensively on football crowd behaviour, policing, and law, largely utilising ethnographic research. In this area he has worked extensively with police forces, governing bodies, stakeholders, and policy makers and has contributed to several influential official reports and inquiries on the subject of football crowd disorder and regulation. Clifford Stott is Professor of Social Psychology at Keele University. He specialises in research on crowds, 'riots', 'hooliganism' and police use of force. He regularly works with police forces and governments internationally advising them on science led and dialogue-based approaches to public order management. In 2021 he was awarded an MBE for the contribution of his work to crowd psychology and in 2015 his work on policing crowds was acknowledged by the ESRC as one of its top 50 achievements in its 50-year history.
Chapter 1 Introduction -- Chapter 2 The Historical Development of Policing and the Law at Football Matches in the UK -- Chapter 3 Legal Measures to Prevent Violence and Disorder at Football -- Chapter 4 Policing A Football Match in The Early 21st Century -- Chapter 5 Risk Supporters? Understanding the Behavioural Norms of Football Fans -- Chapter 6 Understanding the Psychology of Football Crowds -- Chapter 7 Human Rights and Football Policing -- Chapter 8 Understanding Risk in Football -- Chapter 9 Dialogue-Based Approaches to Football Policing -- Chapter 10 The New Agenda: Proposals for Reform in Law and Policing -- Chapter 11 Conclusions.
Keywords: Criminal behavior; Criminology; Psychology; Human rights; International law; Sports-Law and legislation; Criminal Behavior; Crime Control and Security; Behavioral Sciences and Psychology; Human Rights; International Sports Law